Effects of age and spa treatment on match running performance over two consecutive games in highly trained young soccer players - Buchheit, M.; Horobeanu, C.; Mendez-Villanueva, A.; Simpson, B. M.; Bourdon, P. C. (Journal of Sports Sciences, 2011)
The aim of this study was to examine the effect of age and spa treatment (i.e. combined sauna, cold water immersion, and jacuzzi) on match running performance over two consecutive matches in highly trained young soccer players. Fifteen pre- (age 12.8± 0.6 years) and 13 post- (15.9 ± 1 y) peak height velocity (PHV) players played two matches (Matches 1 and 2) within 48 h against the same opposition, with no specific between-match recovery intervention (control). Five post-PHV players also completed another set of two consecutive matches, with spa treatment implemented after the first match. Match running performance was assessed using a global positioning system with very-high-intensity running (> 16.1-19.0 km/h), sprinting distance (>19 km/h), and peak match speed determined. Match 2 very-high-intensity running was "possibly" impaired in post-PHV players (-9 ± 33%; ± 90% confidence limits), whereas it was "very likely" improved for the pre-PHV players (+27 ± 22%). The spa treatment had a beneficial impact on Match 2 running performance, with a "likely" rating for sprinting distance (+30 ± 67%) and "almost certain" for peak match speed (+6.4 ± 3%). The results suggest that spa treatment is an effective recovery intervention for post-PHV players, while its value in pre-PHV players is questionable.